Pengaruh Model Pembelajaran Core Terhadap Kemampuan Penalaran Matematika Peserta Didik Di Kelas VIII SMPN 11 Padang - ZUAIDAH NURI (Jurnal Edukasi dan Penelitian Matematika, 2019)
One of the cognitive abilities that every student must have in mathematical learning is the ability of reasoning. However, the result of preliminary test indicate that the ability of mathematical reasoning student of grade VIII SMP N 11 Padang are still low, and need to be improve. One of the learning models to improve the student’s mathematical reasoning abilities is the Connecting, Organizing, Reflecting, Extending (CORE) learning model. This type of research is quasy experiment with static group design, that involves two sample classes. Experiment classes use CORE learning model and control classes using conventional learning models . Based on the results of data analysis using t test, obtained P-Value = 0,011< a = 0,05. it can be concluded that the mathematical reasoning ability of students who learn by applying the CORE learning model is more better than students who learn by conventional learning. Keywords – CORE Learning Model, Mathematical Reasoning Ability